The Needle not the Spindle? Domestic Training at the London Asylum or House of Refuge for Orphan and Deserted Girls in the Eighteenth Century. (2nd January 2019) - Long, Bridget
Abstract : This article considers the place of The Asylum or House of refuge for orphan and deserted girls amongst other mid eighteenth-century London charitable institutions. It was established in 1758 amid concerns about London's working population not keeping pace with the demands for labour and while campaigners were fighting for the moral wellbeing of the metropolis. The article highlights the role played by some female subscribers who, through a Visiting Ladies committee, provided practical advice to the Guardians for improvements to the running of the institution and the quality of the girls' training. Throughout the century, there was a demand for hand-spun yarn to supply the British textile industry. Poorer girls were taught spinning to meet this demand and so emphasise the perceived female characteristics of diligence and industry. However, needlework, not spinning, was the key component of the girls' daily routine and training at the Asylum.